2014
DOI: 10.1038/ejhg.2014.156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel ARL13B variant in a Joubert syndrome-affected patient with retinal impairment and obesity

Abstract: Joubert syndrome (JS) is a genetically heterogeneous autosomal recessive ciliopathy with 22 genes implicated to date, including a small, ciliary GTPase, ARL13B. ARL13B is required for cilia formation in vertebrates. JS patients display multiple symptoms characterized by ataxia due to the cerebellar vermis hypoplasia, and that can also include ocular abnormalities, renal cysts, liver fibrosis or polydactyly. These symptoms are shared with other ciliopathies, some of which display additional phenotypes, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 33 publications
3
60
0
1
Order By: Relevance
“…Some point mutations in ARL13B are compatible with life and are linked to the human ciliopathy JS (Cantagrel et al ., 2008). Previous studies identified JS patients with homozygous R79Q and Y86C mutations in ARL13B , as well as with an R200C mutation in combination with a truncating mutation (Cantagrel et al ., 2008; Thomas et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Some point mutations in ARL13B are compatible with life and are linked to the human ciliopathy JS (Cantagrel et al ., 2008). Previous studies identified JS patients with homozygous R79Q and Y86C mutations in ARL13B , as well as with an R200C mutation in combination with a truncating mutation (Cantagrel et al ., 2008; Thomas et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As with FTO-deficient individuals, these patients display skeletal and CNS developmental defects that may mask a role of RPGRIP1L in energy homeostasis. A recent report described an obese patient with Joubert syndrome with mutations at ARL13B and similar brain abnormalities as those of individuals with RPGRIP1L-inactivating mutations but with no apparent skeletal anomalies (47), suggesting that CNS abnormalities caused by RPGRIP1L haploinsufficiency may cause obesity in humans.…”
Section: Lepr-bmentioning
confidence: 99%
“…When a mutated ciliary gene leads to Joubert syndrome, obesity is commonly not part of the symptoms. However, recently, a patient with Joubert syndrome and obesity has been reported with a homozygous missense mutation in the ARL13B gene, which affects ciliogenesis (21) . Besides clinical presentation, animal studies may also reveal new interesting genes in this cilia-obesity context.…”
Section: Basal Areamentioning
confidence: 99%
“…Differences have also been observed with regard to the severity and age-of-onset of obesity. Comparing BBS2 patients and BBS4 patients, Carmi et al (129) found that for BBS2 obesity was relatively mild, (99,120) ARL13B* Required for ciliogenesis (21,121) B9D1 Transition zone; basal body BBS19/IFT27/RABL4* Component of the IFT-B particle, plays a role in BBS3 activation during retrograde transport (93) CC2D2A Transition zone; basal body (4,102) CEP19* Transition fibre (98) …”
Section: Pinpointing Obesity To the Basal Area Of The Ciliummentioning
confidence: 99%
See 1 more Smart Citation